(untitled) (Journal of Educational Sciences, 2016)
In the article the author proves the logic of construction of the theory of scientific activity of higher school. This is the section in the theory of education. The pedagogical process of the higher school consists of the processes of education, upbringing, development and research activities. The historical development of universities has accumulated more than this experience of building of the research process at the University. Therefore, on a par with didactics as the theory of education, as well as the theory of education of the higher school, we can offer a selection of the theory of scientific activity of the University. Conditionally there are three stages of development of the content and forms of scientific activity of the institutes of higher education. The first – with the birth of universities to the emergence of research universities; the second – from the nineteenth to the first half of the twentieth century, the third – with the post-war development of higher education at the present time. Identifies eight regularities of scientific activity of the higher school, the principles of scientific activity of higher school. The first pattern: there is dependence of activity of scientific research of the University of the Research Policies of the universities and of the age, and therefore the traditions of the universities. The second rule: in the conditions of growing number of information sources of scientific information is dynamic growth and diversification of scientific research in universities. Third, the scientific activity of the pedagogical process of the higher school depends on the needs of the company and its requirements. Fourth, the processes of training, education, research activity in the higher school of naturally interrelated in a holistic pedagogical process of the University. The fifth rule, the content of the research naturally depends on its objectives and tasks, as well as individual creative and research (analytical) the opportunities of students. Principles of scientific activity of the University: the macro level: the development and implementation of research policy institutes of higher education; academic freedom and the responsibility of the teacher-researcher; integration of science and education; the cultivation of scientific schools and its traditions; creation and development of scientific and innovation environment; the internationalization of scientific research, openness and enhancement of international scientific cooperation and exchanges; dynamism and diversification of the research; the microlevel, the unity of research and teaching, research and training; motivation of scientific activity, the creativity of scientific activity, the success of the training and scientific activity; reflection of science .